Biochemistry of Sleep Quality and Daytime Sleepiness for Employees and University Students: Biokimia Kualitas Tidur dan Rasa Kantuk di Siang Hari untuk Karyawan dan Mahasiswa - Yunus, Tadamoun Sabah (Universitas Muhammadiyah Sidoarjo, 2025)
Background: In the brain, neurotransmitters and hormones interact intricately to control sleep. While adenosine builds up over time to cause tiredness, neurotransmitters like serotonin and norepinephrine encourage wakefulness. Objectives: Measuring the impact of a lack of sleep on daytime sleepiness and daily performance and identifying factors affecting sleep, such as psychological stress, working hours, and daily habits. Methods: This study employs a descriptive, analytical, cross-sectional design. To measure daytime sleepiness and sleep quality, 150 college students were given a self-administered questionnaire. Data on sleep habits and their relationships can be gathered at a single point in time according to the study's cross-sectional design. Descriptive and inferential statistics were utilized to examine the replies, and convenience sampling was employed. Results: Based on the overall statistical results, which include the descriptive statistics for the mean score of 1.52 and a standard deviation of 0.175, the final assessment of sleep quality for individuals is classified as